The English Teaching Strategies For Young Learner in MIN 1 Sikka - Lita Lestari; Rikardus Nasa; Nur Syamsiyah Ekhsan (CV. Alim's Publishing, 2024)
This aims of the research, to find out the teaching strategies used by teachers at MIN 1 Sikka and to find out the implementation process and the problems encountered during the strategy implementation process. This research uses a qualitative method, with the techniques of data collection of observation and interviews. Based on the results of research, it was concluded that, in the learning process there are 5 learning strategies used by the teacher in delivering learning material, namely Case-Based Small Group Discussion strategies, Demonstrations, Games, Independent Study, and Role Play. where the teaching strategy is used, the teacher will go through several different processes in each strategy such as the steps in the implementation process, to the time, class, and material used in each strategy which of course will also be different. As for implementing the learning strategy that has been chosen, there are several problems in the implementation process that teachers will definitely face, especially when the strategy is applied to young learners as students are usually less focused because basically they prefer to play, the class atmosphere is less conducive because students are more choose to play rather than study, and students' pronunciation is still not quite right.